Chapter Paesaggio e musei: sulle tracce di Massimo Quaini - Pressenda, Paola (Territori, 2021)
International policies have recently acknowledged the responsibilities of museums towards the landscape. We trace a critical summary of the debate developed in museology and geography about the relationships between museums and the territories and landscapes surrounding them. As stated by Massimo Quaini, the complex challenge posed by these relationships lies in the balancing between conservation of landscapes and local development: a challenge that in the Italian context could be successfully taken on by eco-museums.